1994
DOI: 10.1002/ijc.2910570506
|View full text |Cite
|
Sign up to set email alerts
|

The induction of apoptosis is a common feature of the cytotoxic action of ether‐linked glycerophospholipids in human leukemic cells

Abstract: The ability of 2 recent ether-lipid derivatives, aza-phospholipids BN52205 and BN52211, to induce apoptosis in different leukemia cell lines was investigated using I-octadecyl-2-methyl-rac-glycero-3- phosphocholine (ET-18-OCH3) as a positive control. HL60, K562, Molt-4 and U937 cells were exposed for 24 hr to 20 microM of drug. The 2 aza-derivatives were as cytotoxic as ET-18-OCH3: BN52205 and BN52211 selectively induced apoptotic death in HL60, Molt-4 and U937 cells, but not in the K562-resistant cell line. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…Testing a larger panel of agents, we have confirmed our earlier finding (Lohmeyer and Workman, 1992) (Munder and Westphal, 1990;Berdel, 1991) PI-3-kinase, the Na+/K+-ATPase, Ca2+ channels and the epidermal growth receptor (Oishi et al, 1988;Kosano and Takatani, 1989;Powis et al, 1992;Berggren et al, 1993 (Honma et al, 1981(Honma et al, , 1991Vallari et al, 1988;Maurer and Hilgard, 1992), but inhibition of differentiation has also been described in the same model system (Shoji et al, 1988;Kuo et al, 1990;Raynor et al, 1991). Apoptosis has been observed in some leukaemic cell lines, including HL60, in response to challenge with ATLs (Diomede et al, 1993(Diomede et al, , 1994, but this response is not universal (Morimoto et al, 1991). (3) As concentrations exceed 40 JAM, the detergent properties of the ATLs begin to induce direct lytic membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…Testing a larger panel of agents, we have confirmed our earlier finding (Lohmeyer and Workman, 1992) (Munder and Westphal, 1990;Berdel, 1991) PI-3-kinase, the Na+/K+-ATPase, Ca2+ channels and the epidermal growth receptor (Oishi et al, 1988;Kosano and Takatani, 1989;Powis et al, 1992;Berggren et al, 1993 (Honma et al, 1981(Honma et al, , 1991Vallari et al, 1988;Maurer and Hilgard, 1992), but inhibition of differentiation has also been described in the same model system (Shoji et al, 1988;Kuo et al, 1990;Raynor et al, 1991). Apoptosis has been observed in some leukaemic cell lines, including HL60, in response to challenge with ATLs (Diomede et al, 1993(Diomede et al, , 1994, but this response is not universal (Morimoto et al, 1991). (3) As concentrations exceed 40 JAM, the detergent properties of the ATLs begin to induce direct lytic membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological inducers included the ether lipids ALP and HePC, 25 the second messengers C 2 -ceramide 26 and the Ca ++ -mobilizing agent thapsigargin. 27 Figure 4 illustrates that H.2 cells were resistant to DEX but equally sensitive as wild-type S49 cells for the induction of characteristic G 2 delay and of hypodiploid cells by the cytostatic drug etoposide.…”
Section: Sensitivity To Pharmacological Inducersmentioning
confidence: 99%
“…In fact we found by GC-MS a high content of alkylglycerol in the capsules offered to the supplemented animals (Table 2B). A study with leukemia patients supplemented with alkylglycerols reported an increased oxidative stress after the nutritional intervention, which the authors pointed as the mechanism behind the increased number of apoptotic neoplastic cells in such patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported a time-and concentrationdependent development of oxidative stress when sensitive HL-60 cells were exposed to membrane-targeted ether lipids [13]. Oxidative stress has been suggested as an inducer of apoptosis in human leukemic cells [14]. Induction of oxidative stress followed by apoptosis is also assumed to explain the inhibition of L-1 sarcoma-induced angiogenesis by alkylglycerols [15].…”
Section: Introductionmentioning
confidence: 99%